2023
DOI: 10.1021/acssuschemeng.3c03163
|View full text |Cite
|
Sign up to set email alerts
|

Coordination Environment Dependent Surface Cu State for CO2 Hydrogenation to Methanol

Abstract: Catalytic conversion of CO 2 with green hydrogen produced from renewable sources into methanol is one of the promising ways to cycle waste CO 2 for carbon neutralization. The activity of Cu-based catalysts for methanol synthesis is closely related to the chemical environment of Cu species, which can be modulated by the special structure of MOFs. It is desired to elucidate the relationship between coordination environment of MOFs and chemical state of confined active metal (e.g., Cu). Herein, we regulate the su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 53 publications
0
6
0
Order By: Relevance
“…Generally, Cu 0 is exposed to the surface of the catalyst and played a fundamental role in the adsorption and activation of H 2 , while Cu + produced by the strong interaction between Cu and the carrier plays a positive role in the adsorption of CO, which effectively improves the selectivity of methanol. ( Samson et al, 2014 ; Song et al, 2023a ). Figure 10B shows the relationship between STY CH3OH and the ratio of Cu + /(Cu + +Cu 0 ), and the relationship between the two was linear, which indicated that Cu + had a greater influence on the performance of the catalyst.…”
Section: Results and Discussion Headingsmentioning
confidence: 99%
See 1 more Smart Citation
“…Generally, Cu 0 is exposed to the surface of the catalyst and played a fundamental role in the adsorption and activation of H 2 , while Cu + produced by the strong interaction between Cu and the carrier plays a positive role in the adsorption of CO, which effectively improves the selectivity of methanol. ( Samson et al, 2014 ; Song et al, 2023a ). Figure 10B shows the relationship between STY CH3OH and the ratio of Cu + /(Cu + +Cu 0 ), and the relationship between the two was linear, which indicated that Cu + had a greater influence on the performance of the catalyst.…”
Section: Results and Discussion Headingsmentioning
confidence: 99%
“…Cu-based catalysts have been widely used in the study of CO 2 hydrogenation to methanol. Scholars generally believe that relatively lowcost copper-based catalysts are promising candidates for carbon dioxide hydrogenation to methanol (Song et al, 2023a;Han et al, 2023;Zhang et al, 2023). However, Cu-based catalysts still face the problem of low activity and low stability (Xu et al, 2022;Chen et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…One distinct advantage of carbon materials is their ability to act as reducing agents during thermal treatments while securing the metallic particles . This feature is crucial since the metallic phase often serves as the active sites for CO hydrogenation . Iron and cobalt catalysts anchored on carbon structures have demonstrated superior FTS activity when juxtaposed with their oxide-supported counterparts, resulting from the potential electron transfer between carbon and the metals …”
Section: Introductionmentioning
confidence: 99%
“…Metal–organic frameworks (MOFs) have been considered as reliable materials consisting of metal ions or metal-oxo clusters coordinated with organic ligands with their uniform tunable porosity and better-defined local structure, opening new opportunities across several remarkable functions, including the gas sensor, capture, separation, and catalysis. Taking advantage of their diversities in synthetic tunability, devising permanently porous structures bearing functional catalytically active units that confine and interact well with specific reactants has become a novel strategy for catalyst design. , Recently, MOF-based catalysts have been employed for the low-cost and rational design of catalytic sites and widely used in various reactions, particularly, in the catalytic hydrogenation of CO 2 . …”
Section: Introductionmentioning
confidence: 99%